Justice and Sustainability: Legal Perspectives on Mining and Tourism in Raja Ampat - Mulyani, Basri; Helmi, M. (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
The centralization of mining management as stipulated in Law Number 2 of 2025 concerning Mineral and Coal Mining has created various problems in its implementation, including environmental damage, corruption of mining permits, and degradation of the existence of indigenous communities. In the context of the implementation of regulations on mining permit management in tourism areas, as occurred in Raja Ampat, it threatens the existence of sustainable tourism that depends on the natural beauty and diversity of marine biota. This research is a normative legal research that also orients the socio-legal aspects to assess the impact of mining exploration permits in the Raja Ampat tourism area. The approach used in this research is a statutory regulatory approach and a conceptual approach. The purpose of this study is to explain the urgency protection law to area tourism based natural from activity extractive mining. The results of this study confirm that mining activities in the Raja Ampat tourism area are contradictory and cannot go hand in hand because the existence of mining in the Raja Ampat tourism area degrades the environment that is the backbone of ecotourism-based tourism. Protection of sustainable tourism areas from mining activities is urgently carried out by including the Raja Ampat tourism area in a conservation area as regulated in Law Number 1 of 2014 concerning Amendments to Law Number 27 of 2007 concerning Management of Coastal Areas and Small Islands and the Constitutional Court Decision Number 35/PUU-XXI/2023, which affirms that small islands and coastal areas must be protected from extractive activities such as mining to preserve environmental sustainability and the rights of local communities.